Modeling of project activities for UAV modernization to conduct swarm drone attack missions - Oleg Fedorovych; Leonid Malieiev; Oleksii Hubka; Andrei Popov (Авіаційно-космічна техніка та технологія)
This study addresses the critical issue of modernizing existing unmanned aerial vehicles (UAVs) to enhance their applicability in the contemporary conditions of hybrid warfare. The research focuses on adapting the structural design of UAVs through reengineering, enabling their deployment in swarm attack operations against high-priority enemy targets. Thus, this publication explores the essential measures for planning project activities related to UAV modernization, aiming to align their capabilities with the operational needs of military forces on the battlefield. The primary objective of this study is to develop a comprehensive set of mathematical and simulation models that facilitate the planning of UAV modernization projects. The models are intended to optimize new functions related to control, coordination, and navigation, enabling UAVs to perform as part of drone swarms in military missions. This research analyzes the existing challenges in reengineering high-tech systems for evolving operational environments and presents possible UAV reengineering strategies. A particular emphasis is placed on the component-based approach to designing new UAVs or upgrading existing ones. The study categorizes UAV components into three types within the architecture of modern high-tech systems: existing components, components requiring modernization, and newly developed components. The findings highlight the necessity of balancing the reuse of existing components with the integration of innovative technologies. While innovative components enhance UAV capabilities, they also increase project duration, costs, and associated risks – factors that are particularly critical during a state of war. This study also examines the currently deployed UAV models to assess their suitability for modernization projects. In the initial stages of UAV modernization, expert assessments from specialists in complex system manufacturing and military operations are used to evaluate and rank potential modernization options. These qualitative evaluations, represented as linguistic variables, were processed using the lexicographic ordering of alternatives to identify the most reasonable option for implementation. Integrating new components into existing UAV architectures necessitates optimizing reengineering decisions under constraints such as limited time, budget, and heightened risks due to national security conditions. To address this, an optimization model based on integer (Boolean) programming was developed for selecting the most rational UAV component architecture. Additionally, significant attention is given to structuring the sequence of project activities, estimating the project completion time, and evaluating the risks associated with UAV modernization. A simulation model was constructed to analyze the lifecycle of new UAV components or the modernization of existing ones within a specified time scale. The entire modernization project was also simulated to assess the feasibility and efficiency. Using the agent-based platform AnyLogic, interactive simulation modeling of the UAV modernization processes was conducted. The scientific novelty of this research lies in the development of original models that enable comprehensive UAV analysis for modernization. These models facilitate the selection of new UAV components, assess modernization project timelines and risks, and apply simulation modeling to evaluate the sequence of project activities. The research findings provide a foundation for planning UAV modernization processes to enhance their operational effectiveness in modern hybrid warfare. By integrating aerial operations with ground-based military actions, this approach contributes to strengthening national defense capabilities.